QTc prolongation and diastolic dysfunction in cirrhosis patients with higher Child-Pugh score - Chandrakant Salve,; Jaiprakash Kuldeep,; Dinesh Singh Mahor, (Asian Journal of Medical Sciences, 2023)
Background: Cirrhosis is associated with numerous cardiac abnormalities, which include increased cardiac output, left ventricular diastolic dysfunction, increased wall thickness of cardiac chambers, and pulmonary arterial hypertension. Without further identified cardiac disorders, cirrhotic cardiomyopathy (CCM) is a chronic cardiac dysfunction with an impaired contractile reaction to stress stimuli, impeded diastolic relaxation, and electrophysiological anomalies with a prolonged QT interval. In chronic hepatic disease, echocardiography is a non-invasive method for detecting CCM. Aims and Objectives: The focus was to examine the link between cardiac dysfunction and conduction disturbances in cirrhosis individuals and the extent of the disorder. Materials and Methods: A case–control investigation was conducted at a Medical College. The research involved a cohort of 50 patients and an equal number of 50 healthy controls. The Child-Pugh (CP) Score was utilized to evaluate the degree of liver cirrhosis severity. Bazett’s formula was utilized to compute the QTc interval. The 2D echocardiography revealed the presence of diastolic dysfunction, as evidenced by the E/A ratio. Results: Of 50 patients, 37 (74%) were male, 13 (26%) were female, and the mean age of the patients was 51.76±9.89 years. The E/A ratio in the control group had a mean value of 1.10±0.19, whereas in the cases, it had a mean value of 0.94±0.20. A statistically significant relationship was observed between the control and cases, with a P-value of less than 0.0001. QTc interval between control with a mean value of 382.9±47.34 ms and cases with a mean value of 431.6±62.84 ms was found statistically significant with P<0.0001. Conclusion: QTc prolongation and transmitral flow abnormality are markers of severe cardiac abnormality in patients with higher CP score in cirrhosis. Hence, recognition of such abnormalities in cirrhotic patients may prevent arrhythmogenic cardiovascular deaths in such patients.